Atomoxetine for the treatment of Attention-Deficit/Hyperactivity Disorder (ADHD) in children with ADHD and dyslexia - Rubin Richard; Greenbaum Michael; Gathercole Susan; Sumner Calvin R; Williams David; Hollandbeck Millie; Wietecha Linda (BMC, 2009)
Abstract Background The objective of this study was to assess the effects of atomoxetine on treating attention-deficit/hyperactivity disorder (ADHD), on reading performance, and on neurocognitive function in youth with ADHD and dyslexia (ADHD+D). Methods Patients with ADHD (n = 20) or ADHD+D (n = 36), aged 10-16 years, received open-label atomoxetine for 16 weeks. Data from the ADHD Rating Scale-IV (ADHDRS-IV), Kaufman Test of Educational Achievement (K-TEA), Working Memory Test Battery for Children (WMTB-C), and Life Participation Scale for ADHD-Child Version (LPS-C) were assessed. Results Atomoxetine demonstrated significant improvement for both groups on the ADHDRS-IV, LPS-C, and K-TEA reading comprehension standard and composite scores. K-TEA spelling subtest improvement was significant for the ADHD group, whereas the ADHD+D group showed significant reading decoding improvements. Substantial K-TEA reading and spelling subtest age equivalence gains (in months) were achieved for both groups. The WMTB-C central executive score change was significantly greater for the ADHD group. Conversely, the ADHD+D group showed significant phonological loop score enhancement by visit over the ADHD group. Atomoxetine was well tolerated, and commonly reported adverse events were similar to those previously reported. Conclusions Atomoxetine reduced ADHD symptoms and improved reading scores in both groups. Conversely, different patterns and magnitude of improvement in working memory component scores existed between ADHD and ADHD+D patients. Though limited by small sample size, group differences in relation to the comparable changes in improvement in ADHD symptoms could suggest that brain systems related to the therapeutic benefit of atomoxetine in reducing ADHD symptoms may be different in individuals with ADHD+D and ADHD without dyslexia. Trial Registration Clinical Trial Registry: ClinicalTrials.gov: NCT00191048